2012
DOI: 10.4161/adna.23842
|View full text |Cite
|
Sign up to set email alerts
|

Templating effect in DNA proximity ligation enables use of non-bioorthogonal chemistry in biological fluids

Abstract: Here we describe the first example of selective reductive amination in biological fluids using split aptamer proximity ligation (StAPL). Utilizing the cocaine split aptamer, we demonstrate small-molecule-dependent ligation that is dose-dependent over a wide range of target concentrations in buffer, human blood serum and artificial urine medium. We explore the substrate binding preferences of the split aptamer and find that the cinchona alkaloids quinine and quinidine bind to the aptamer with higher affinity th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The addition of ligand reduced the k ex of imino protons close to the binding site, but it has little effect on resonances distant from the binding site. For example, G29 is located at the binding site of the aptamer, and its k ex value reduces from (50 5 6) s À1 in the free state of MN4 at 10 C to 15 When comparing quinine-and cocaine-bound MN4, we and others have shown that quinine binds $50-fold tighter than cocaine (15,23,25,27,(47)(48)(49). When looking at the k ex values of quinine-and cocaine-bound MN4, we generally observe little difference between these two bound aptamers at low temperatures.…”
Section: Discussionmentioning
confidence: 95%
“…The addition of ligand reduced the k ex of imino protons close to the binding site, but it has little effect on resonances distant from the binding site. For example, G29 is located at the binding site of the aptamer, and its k ex value reduces from (50 5 6) s À1 in the free state of MN4 at 10 C to 15 When comparing quinine-and cocaine-bound MN4, we and others have shown that quinine binds $50-fold tighter than cocaine (15,23,25,27,(47)(48)(49). When looking at the k ex values of quinine-and cocaine-bound MN4, we generally observe little difference between these two bound aptamers at low temperatures.…”
Section: Discussionmentioning
confidence: 95%
“…One feature of the cocaine-binding aptamer that sets it apart from other aptamers is its binding promiscuity. Though selected for cocaine binding, this aptamer also binds other alkaloids and even binds quinine with higher affinity than it binds cocaine. Such versatility in ligand binding is uncommon among aptamers and is not a desirable characteristic for a biosensor, but it may be a useful property for the biotechnology applications of the cocaine-binding aptamer. The binding versatility of this aptamer leads to questions such as “How does the same sequence bind to different ligands?” and “Does the aptamer use the same binding site and binding mechanism for all ligands?” In this study, we investigate the interaction of the cocaine-binding aptamer with quinine.…”
mentioning
confidence: 99%
“…Most aptasensors are designed to take advantage of the binding mechanism of the aptameric probe to generate a signal from target binding. The majority of cocaine aptasensors reported in the literature rely on one of the structure-switching aptamer constructs for this reason. ,, Our goal in the design of EMPAS-based aptasensors has always been to try and provide more universality in a sensing platform that would function with not only structure-switching aptamers but also rigid secondary structure variants. The main difference between our two EMPAS-based aptasensors, M6CA and M4CA, is the nature of the immobilized aptameric probe (Figure A).…”
Section: Discussionmentioning
confidence: 99%
“…Another structure-switching mechanism consists in splitting the aptamer into two or more strands that will come together in the presence of cocaine, inducing secondary structure formation and tertiary folding in the process. This mechanism is referred to as “split aptamer ligation” and is the foundation upon which most cocaine aptasensors are based. ,, As evident with the cocaine aptamer example, there is a need for a more universal transduction technique that will function with different aptamer binding mechanisms.…”
mentioning
confidence: 99%